2021
DOI: 10.1093/eurheartj/ehab075
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of myocardial injury in recovered troponin-positive COVID-19 patients assessed by cardiovascular magnetic resonance

Abstract: Background Troponin elevation is common in hospitalized COVID-19 patients, but underlying aetiologies are ill-defined. We used multi-parametric cardiovascular magnetic resonance (CMR) to assess myocardial injury in recovered COVID-19 patients. Methods and results One hundred and forty-eight patients (64 ± 12 years, 70% male) with severe COVID-19 infection [all requiring hospital admission, 48 (32%) requiring ventilatory suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
344
4
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(436 citation statements)
references
References 38 publications
28
344
4
10
Order By: Relevance
“…Since December 2019, SARS-CoV-2 has infected over 167 million people worldwide [11]. Cardiac injury, including myocardial infarction, myocarditis, and stress cardiomyopathy, was prevalent in hospitalized patients and portended a worse prognosis [4][5][6]. Myocarditis is defined as myocardial inflammation with histological evidence of inflammatory infiltrates and evidence of necrosis, and may be the result of a variety of etiologies including infections and toxins [12].…”
Section: Discussionmentioning
confidence: 99%
“…Since December 2019, SARS-CoV-2 has infected over 167 million people worldwide [11]. Cardiac injury, including myocardial infarction, myocarditis, and stress cardiomyopathy, was prevalent in hospitalized patients and portended a worse prognosis [4][5][6]. Myocarditis is defined as myocardial inflammation with histological evidence of inflammatory infiltrates and evidence of necrosis, and may be the result of a variety of etiologies including infections and toxins [12].…”
Section: Discussionmentioning
confidence: 99%
“…Small cohort studies utilizing cardiac MRI have reported conflicting results 4,5 , further highlighting the need to better elucidate potential long-term cardiac sequelae of COVID-19, especially as it pertains to patient symptoms and functional impairments. Furthermore, no data presently exist to support or refute the cardiovascular impact of COVID-19 in patients with or without pre-existing cardiac conditions.…”
Section: Cardiac Complications Of Covid-19mentioning
confidence: 99%
“…Among 148 hospitalised patients with severe COVID-19 infection and elevated troponin, outpatient CMR was performed ∼2 months following diagnosis or discharge (60). This showed normal LVEF in 89% of patients, LGE or ischaemia in 54% of patients, of whom 26% had a non-ischaemic pattern and 22% had an ischaemic pattern, and dual pathology was seen in 6%.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%